Core competencies for highway safety professionals. - Jovanis, Paul; Gross, Frank (Research results digest (National Cooperative Highway Research Program), 2006)
"This digest summarizes the results of a study conducted by Paul Jovanis and Frank Gross, Pennsylvania State University."